Hepatectomy versus transcatheter arterial chemoembolization for resectable BCLC stage A/B hepatocellular carcinoma beyond Milan criteria: A randomized clinical trial - Fang, Chongkai; Luo, Rui; Zhang, Ying; Wang, Jinan; Feng, Kunliang; Liu, Silin; Chen, Chuyao; Yao, Ruiwei; Shi, Hanqian; Zhong, Chong (Frontiers in Oncology, 2023)
Background. Hepatectomy is the recommended option for radical treatment of BCLC stage A/B hepatocellular carcinoma (HCC) that has progressed beyond Milan criteria. This study evaluated the efficacy and safety of preoperative neoadjuvant transcatheter arterial chemoembolization (TACE) for these patients. Methods. In this prospective, randomized, open-label clinical study, BCLC stage A/B HCC patients beyond Milan criteria were randomly assigned (1:1) to receive either neoadjuvant TACE prior to hepatectomy (NT group) or hepatectomy alone (OP group). The primary outcome was overall survival (OS), while the secondary outcomes were progression-free survival (PFS) and adverse events (AEs). Results. Of 249 patients screened, 164 meeting inclusion criteria were randomly assigned to either the NT group (n = 82) or OP group (n = 82) and completed follow-up requirements. Overall survival was significantly greater in the NT group compared to the OP group at one year (97.2% vs. 82.4%), two years (88.4% vs. 60.4%), and three years (71.6% vs. 45.7%) (p = 0.0011) post-treatment. Similarly, PFS was significantly longer in the NT group than the OP group at one year (60.1% vs. 39.9%), two years (53.4% vs. 24.5%), and three years (42.2% vs. 24.5%) (p=0.0003). No patients reported adverse events of grade 3 or above in either group. Conclusions. Neoadjuvant TACE prolongs the survival of BCLC stage A/B HCC patients beyond Milan criteria without increasing severe adverse events frequency.